Analysis of the Impact of Balance Between Work and Study on Student Learning Productivity STIKOM Tunas Bangsa Pematangsiantar - Hafizah Rahmi Lubis; Wanda Eka Nugraha; Zaskia Aulia Zahra; Ferdinand Saragih; Victor Asido Elyakim P (Yayasan Literasi Sains Indonesia, 2025)
Working while studying has become a common phenomenon among students, especially due to the increasing cost of living and education. A balance between study and work is essential to maintain learning productivity, especially for students who are also active in campus organizations. However, many students have difficulty managing their time, which can lead to stress, fatigue, and decreased academic quality. This study highlights the challenges faced by working students, such as high workload, academic demands, and lack of rest time. With good time management, such as creating a clear schedule and utilizing free time effectively, students can achieve a better balance between study and work. Therefore, it is important for students to develop optimal time management strategies to maintain learning productivity and achieve academic success